A relação entre ouvintes assíduos e o rádio: um estudo de usuários da informação a partir de uma perspectiva compreensiva - Marina Torres Pessoa (2010)
Presents an analysis of the relationship established between regular radio listeners and radio. For this, it uses the contributions of studies of information users, adopting a comprehensive perspective in line with the proposal to expand the agenda of the field. It discusses the issues involved in listening to radio from the perception of listeners. In-depthinterviews with 15 people whose daily listen to radio supported the analysis. Analysis of data collected is organized into eight topics: company and affection; emotion; identification; imagination; learning; interaction; agility and mobility; habit. This study relates variousaspects of the relationship radio/listener to the emotional, social, creative and existential dimensions of radio information. Highlights the complexity of information processes and the importance of a comprehensive approach to the analysis of such processes